Studies on Etiologies and Hemato-Biochemical Alterations Associated with Anemia in Goats - Rao, Neha; Parmar, Jignesh J.; Sadhu, Dasharath B.; Shah, Aditya I.; Patel , Deepak M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present investigation was carried out to study the incidence and etiological factors, including Hemato-biochemical changes  associated with Anemia in goats presented at Veterinary Clinical Complex of the College of Veterinary Science and Animal Husbandry  Anand for 2 years. Total 559 goats were suspected of Anemia, and 80 (14.31 %) goats were found anaemic. Sex-wise incidence was  higher in females (72.50%, 58/80) than males (27.50%, 22/80). Age-wise incidence was higher in ≥1-year age group (66.25%, 53/80) as  compared to
Keywords: Anemia; Etiology; Goats; Hemato-biochemical profile; Incidence